Evaluation of Parking Performance at Semut Station Surabaya - Sugiarti Sugiarti; Sri Wiwoho Mudjanarko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
Parking is one element of the facility that cannot be separated from the system road transport as a whole. With the increase in the population of a city, this will lead to an increase in the need to carry out various activities. Semut Station Surabaya is one of the public facilities with a fairly high level of activity. However, in reality the parking lot at the Surabaya Semut Station is often full and disturbing the surrounding traffic. Therefore, it is necessary to analyze the performance capacity and parking space at the Surabaya Semut Station. The method used is first conducting a literature study on parking, a preliminary survey at the studied site, collecting primary data and secondary data, then proceed with data analysis in the form of performance capacity and parking space. The results of this study show that the parking characteristic have a maximum parking volume of 247 motor bikes/day and 160 cars/day, the average duration of parking for motor bikes is 5.66 hours and cars is 4.62 hours, the maximum parking accumulation for motor bikes is as much as 87 vehicles/day and 64 cars/day, the maximum parking index for motorbikes and cars are 2.18% and 2.56% respectively, and the parking space requirement for motorcycles (SRP) is 95 SRP and for cars is 52 SRP.